2008
DOI: 10.2146/ajhp070620
|View full text |Cite
|
Sign up to set email alerts
|

Current issues in pharmaceutical reimbursement

Abstract: An understanding of issues in the current health care environment arising from recent and proposed changes in Medicare rules and rates for pharmaceutical reimbursement can help position pharmacists to manage these issues.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 8 publications
0
6
0
Order By: Relevance
“…In this program, pharmacists are remunerated for providing professional medication and disease management services to patients with asthma/COPD [21]. In the US, diagnosis-specific services provided by pharmacists are well developed under Medicare, the health program for elderly patients, and under Medicaid, the health program for individuals with low incomes [23]. In Australia, the Pharmacy Asthma Management Service involves pharmacists conducting regular consultations with patients suffering from asthma.…”
Section: Specific Ppsmentioning
confidence: 99%
“…In this program, pharmacists are remunerated for providing professional medication and disease management services to patients with asthma/COPD [21]. In the US, diagnosis-specific services provided by pharmacists are well developed under Medicare, the health program for elderly patients, and under Medicaid, the health program for individuals with low incomes [23]. In Australia, the Pharmacy Asthma Management Service involves pharmacists conducting regular consultations with patients suffering from asthma.…”
Section: Specific Ppsmentioning
confidence: 99%
“…In general, pharmacists view PAPs as a means to implement cost-avoidance measures as well as improve medication access for patients. 53 The problem of medication access is multi-factorial, and yet people from pharmacy and medicine—the disciplines that are often focused on clinical practice and patient care—may have limited time and resources for conducting research. Previous research has shown associations between study quality and study funding; 54,55 therefore clinical practitioners need multidisciplinary collaborations with researchers from other disciplines (e.g., public health) concerned with medication access and affordability issues to be competitive scientists and successful in obtaining research funding.…”
Section: Discussionmentioning
confidence: 99%
“…The US Federal Government does not require PAPs, but manufacturer companies do receive significant tax breaks. PAPs increase access to medications for individuals who cannot afford these high-cost medications [ 21 ]. By 2016, an estimated $US180–190 billion (i.e., 15–16 %) savings for patients, payers, drug wholesalers, and distributors will be achieved through discounts and rebates on brand name medications [ 8 ].…”
Section: Cost and Utilization Strategies For Specialty Pharmaceuticalmentioning
confidence: 99%
“…These rebates create cost savings and are typically available for specialty pharmaceutical classes with higher utilization, such as those agents for rheumatoid arthritis and MS as well as growth hormones [ 3 , 23 ]. Specialty pharmacies also help payers control drug costs by only providing medications for individuals who meet regulated indications for these high-cost drugs [ 21 ].…”
Section: Cost and Utilization Strategies For Specialty Pharmaceuticalmentioning
confidence: 99%